(untitled) (Journal of Medical & Health Sciences Review, 2025)
The digestive system of cow, specifically rumen has complex and diverse ecosystem that has a significant impact on the breakdown of plant-based compounds, fermentation and absorption of nutrients. The purpose of this study was to analyze the structure, variety and functioning of rumen bacteria involved in the digestion of cow by using 16srRNA sequencing. This study provides the deep insight of bacteria involvement in digestion of cow, by identifying the composition of microbial community and their metabolic role. Genomic DNA was isolated using a fecal sample and amplified via PCR to target the 16S rRNA region of gene. After library construction and quantification sequencing was performed on the DNBSEQ platform. The raw information was filtered by eliminating poor-quality reads, adapters, sequence with low ambiguous bases and low complexity areas. 97.83% of original sequence was obtained as high-quality reads representing the excellent data integrity. Paired end reads overlapped with each other to create consensus tags for further analysis. Tags were clustered to OTU (operational taxonomic unit) with 97% similarity, producing 326 distinct OTUs in the sample. By using the Ribosomal Database project (RDP) and green-genes database taxonomic classification was performed indicated the presence of diverse microbial bacterial groups that are commonly found in ruminants. The key taxa are Oscillospiraceae, Lachnospiraceae, Bacteroidaceae, and Erysipelotrichaceae. These bacteria are recognized for their significant contributions to the production of volatile fatty acid (VFAs), fermentation of fiber, and degradation of cellulose.